7 - Industrialisation et stratégie des besoins sociaux en Algérie - Abdelmadjid BOUZIDI (Africa Development, 1985)
Meeting the basic needs of the Algerian people has never been seriously considered as a major objective by Algerian planners. It has been and still is the planners argument that the basic needs could be met by in vesting more in productive sectors of the economy, mainly in industry. In this paper, the author tries to look into the Algerian approach to meeting the basic needs of the people as it was spelt out in 1966. He then evaluates it after 15 years of implementation and finally studies the new orientations that the approach seems to take since the 1980—1984 five year plan. On the first point, the author argues thai the 1966 plan was basi cally a long-term one which tried to select the projects that could be im plemented within a generation from those that cov.'d not be implemented within this period. The Algerian planners therefore decided on the follow ing orientations: 1. To maximize the rate of economic growth; 2. to devote the bulk of national wealth to investment; 3. to give priority to investments which are immediately productive, i.e. in industry. 4. to meet some priority basic needs through a systematic action by the state. These priority ' asic needs relate to employment, education, régio nal equilibrium and social justice. For the Algerian planners all the other basic needs such as those related to health, housing, water, electricity and gaz are necessary but not of priority. Evaluating the implementation of the basic needs stmtegy in Algerian. the author concludes that the strategy failed to reach the goals which the planners set. Because of that failure, new goals were set in 1979 for the 1980^1984 five year plan. The new priority goals are to improve the management of the economy and also to seriously cater for the basic needs of the Algerian people in order to make-up for the delay and improve their life conditions.